The effect of company size and inventory intensity on tax aggressiveness with political connections as a moderating variable in agricultural sector companies listed on the BEI for the period 2019-2023 - Pratama, Dewi Amalia Cipta; Rusdiansyah, Nurul; Rosyidah, Dania Meida; Heliani, Heliani (Journal of Accounting Auditing and Business, 2025)
This study aims to analyze the effect of company size and inventory intensity on tax aggressiveness with political connections as a moderating variable in agricultural sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The research method used is quantitative analysis with multiple linear regression analysis methods involving 40 companies selected through purposive sampling techniques. The analysis shows that company size and inventory intensity significantly influence tax aggressiveness. In addition, political connections have been proven to moderate the relationship between company size, inventory intensity, and tax aggressiveness. This finding suggests that companies with political connections tend to aggressively take advantage of their position to reduce the tax burden. This study contributes to the accounting literature by highlighting the important role of political connections in corporate tax management strategies. The practical implication of this research is the need for stricter regulations to minimize opportunities for abuse of tax policies by politically connected companies.